The Influence of Market, Technical, Management, and Financial Aspects on the Feasibility of Photocopy Service Businesses - Mustari Mustari; Nur Arisah (Citakonsultindo, 2026)
This study examines the influence of Market Aspects (AP), Technical Aspects (AT), Management Aspects (AM), and Financial Aspects (AK) on Business Feasibility (KU) of photocopy service enterprises located around educational areas in Makassar City. A quantitative approach using PLS-SEM was employed with 100 photocopy business owners as respondents. The results show that all research instruments are valid and reliable, and the model obtained an R² value of 0.741, indicating that 74.1% of business feasibility is explained by the four variables. Partially, Market Aspects, Technical Aspects, and Financial Aspects have a positive and significant effect on business feasibility, while Management Aspects show no significant effect. These findings indicate that the feasibility of photocopy businesses is primarily determined by market strength, technical readiness, and financial conditions.